The Effect of Types and Doses Compost Fertilizer on Ylang Ylang (Cananga odorata forma genuina) Seedling Growth - Istomo Istomo; Ariyani Pramudita Utami (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2022)
Savanna is the icon of Baluran National Park. The endemic species of Bekol Savana is bekol or bidara (Ziziphus mauritiana Lamk.). Emerge complication instant exotic like Acacia nilotica spread in Savanna for nature fire burning partition plant. Growth of A. nilotica is invasive so can be change nature conditition of savanna. The goals are to know composition structure and pattern distribution of Z. mauritiana in raise savanna and invasive savanna. Examination did with rectangular plot of analisis vegetation as purposive sampling in wide 20 m x 60 m in 10 plot each location. The result shows the structure in raise savanna is opened area and have density of grass is abundant than density tree is low and the invasive savanna is change to be closed A. nilotica forest. Density of Z. mauritiana in raise savanna is more which 3 364/ind/ha than invasive savanna is 260 ind/ha. Pattern distribution of Z. mauritiana in Bekol Savanna is clumped. Biofisic factors can be straddling of Z. mauritiana are open area, clay loam teksture, alkaline pH and arid season. Keywords: Bekol Savanna in Baluran National Park, Bidara (Z. mauritiana), pattern distribution, structure